PEMBUKTIAN HUKUM WANPRESTASI DALAM PERJANJIAN NON-DISCLOSURE AGREEMENT - Marsanda Dista Bitha; Emi Zulaika; Edi Wahjuni; Ajeng Pramesthy Hardiani Kusuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
A Non-Disclosure Agreement (NDA) is an agreement between a company and an employee intended to protect all of the company’s confidential information from being disclosed to third parties, particularly companies engaged in the same line of business. A failure by either party to fulfill their agreed-upon obligations will result in a breach of contract that requires legal proof. The research methodology employed in this study utilizes a normative legal approach through a literature review, supplemented by the South Jakarta District Court decision No. 666/Pdt.G/2024/PN.JKT.SEL as a real-world case example regarding breach of a Non-Disclosure Agreement. This study aims to identify the process and challenges of proving breach of a Non-Disclosure Agreement and to determine the legal consequences that may arise from such a breach. The process of proving breach of contract is carried out by submitting evidence to the competent court. The legal consequences that may arise from a breach of a Non-Disclosure Agreement include reimbursement of costs, damages, and interest in accordance with the provisions of Article 1243 of the Civil Code, as well as the imposition of additional sanctions in the form of imprisonment for a maximum of 2 years and/or a fine of up to 300 million rupiah in accordance with the provisions of Article 17(1) of Law No. 30 of 2000 on Trade Secrets.